Modular Measuring System for Assesment of the Thyroid Gland Functional State - Vladimir Rosik; Milan Tysler; Jana Svehlikova; Jaroslav Zdinak (Advances in Electrical and Electronic Engineering, 2005)
Distributed modular system BioLab for biophysical examinations enabling assessment of the thyroid gland functional state is presented in the paper. The BioLab system is based on a standard notebook or desktop PC connected to an Ethernet-based network of two smart sensors. These sensors are programmed and controlled from PC and enable measurement of selected biosignals of the human cardiovascular and neuromuscular system that are influenced by the production of thyroid gland hormones. Recorded biosignals are processed in a PC and peripheral indicators characterizing thyroid gland functional state are evaluated.